A theoretical model for predicting the temperature-dependent fatigue crack propagation threshold of nickel-based superalloys. (April 2022) - He, Yi; Li, Weiguo; Yang, Mengqing; Zhao, Ziyuan; Zhang, Xuyao; Dong, Pan; Ma, Yanli
Highlights: A temperature-dependent fatigue propagation criterion was proposed. A maximum energy density related to the fatigue crack propagation was put forward. A temperature-dependent fatigue crack propagation threshold model was developed. Model predictions were in good agreement with experimental for eleven superalloys. Achieved convenient prediction of fatigue threshold values at elevated temperatures. Abstract: The fatigue crack propagation threshold is an essential predictor for the safety of crack-containing components during their expected life. In this work, the fatigue crack propagation of a material is considered from an energy perspective and a critical energy density related to fatigue propagation was presented. A temperature-dependent crack fatigue propagation criterion was proposed. The temperature-dependent fatigue crack propagation threshold model for superalloys was developed. The model reveals the quantitative relationship between fatigue crack propagation threshold, Young's modulus, and temperature. The model predictions were in good agreement with all the available experimental data for eleven superalloys. A convenient and simple optional method for predicting the fatigue crack propagation threshold of superalloys at elevated temperatures was achieved. In addition, the limitations and applicability of the model are discussed. The results of the research are of potential application to aero-engine structural integrity studies.